2009
DOI: 10.1183/09031936.00193908
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia risk in COPD patients receiving inhaled corticosteroids alone or in combination: TORCH study results

Abstract: Inhaled corticosteroids (ICS) are important in reducing exacerbation frequency associated with chronic obstructive pulmonary disease (COPD). However, little is known about the risk of associated infections.In a post hoc analysis of the TOwards a Revolution in COPD Health (TORCH) study, we analysed and identified potential risk factors for adverse event reports of pneumonia in this randomised, double-blind trial comparing twice-daily inhaled salmeterol (SAL) 50 mg, fluticasone propionate (FP) 500 mg, and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
303
9
10

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(345 citation statements)
references
References 36 publications
23
303
9
10
Order By: Relevance
“…Growth suppression is dose and device dependent and has been reported with low to medium doses of BDP MDI (34) and BUD dry-powder inhaler (DPI) (70,71) in children 4 to 17 years of age and in infants 2 years of age or younger with FP MDI plus VHC (14) but not with low-to medium-dose FP DPI, mometasone furoate DPI, or ciclesonide MDI (71). Several large studies have shown that ICS alone or in combination is associated with increased pneumonia risk and even death from pneumonia, with a dose-related risk (28,55,72,73).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Growth suppression is dose and device dependent and has been reported with low to medium doses of BDP MDI (34) and BUD dry-powder inhaler (DPI) (70,71) in children 4 to 17 years of age and in infants 2 years of age or younger with FP MDI plus VHC (14) but not with low-to medium-dose FP DPI, mometasone furoate DPI, or ciclesonide MDI (71). Several large studies have shown that ICS alone or in combination is associated with increased pneumonia risk and even death from pneumonia, with a dose-related risk (28,55,72,73).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…The risk was evident, especially in the elderly and in those with more severe disease and lower lung function. However, in this metaanalysis data on elderly seems limited, because information only derives from a post-hoc analysis of the TORCH (TOwards a Revolution in COPD Health) trial [60]. In this trial, the hazard ratio for pneumonia increased from 1.62 for patients aged 55-64 years to 2.18 for patients aged C75 years, in comparison with those \55 years.…”
Section: Pneumoniamentioning
confidence: 99%
“…In various clinical trials, the use of ICs in isolation or in combination with LABAs increased the adverse effects, principally the risk of developing pneumonia, when compared with the use of a placebo. (43,64,79) However, a study evaluating those same drug combinations showed that the medications had no impact on the risk of developing pneumonia. (47) The use of ICs has not been shown to increase the risk of …”
Section: Adverse Drug Effectsmentioning
confidence: 99%
“…(32) In contrast, an observational study compared those same medications and found no differences regarding cardiac ischemic events, arrhythmias, or pneumonia. (68) The use of fluticasone was compared with that of salmeterol in isolation, (19,20,43,79) as well as with that of LAMAs in isolation, (69) and was shown to increase the risk of developing pneumonia.…”
Section: Mortalitymentioning
confidence: 99%